1244 Evaluation of patient characteristics in a cohort of young people presenting to a tertiary paediatric post COVID-19 outpatient service. (17th August 2022) - Juste, Maude; Wortley, Elizabeth; Whittaker, Elizabeth; Baig, Benjamin; Segal, Terry; Goddings, Anne-Lise
Abstract : Aims: Post-COVID syndrome (also referred to as Long COVID) is a novel condition defined by symptoms associated with COVID-19 persisting more than three months following an initial infection with no alternative diagnosis, and have an impact on function. 1 It is being increasingly observed in children and young people (CYP), and the long-term prevalence of this condition is, as yet, unknown. The Pan-London CYP Post-COVID Service was set up in April 2021 to provide a multidisciplinary 'hub and spoke' model of care to this novel group of patients, both virtual and face to face. This service evaluation reviews the patients who have been referred to the service to date. Peer-reviewed literature about post-COVID syndrome in CYP is limited and can appear conflicting, as the symptomatology and co-morbidities of CYP are different to the more established evidence from adults. As such, evaluating our patient population, service provision and multi-disciplinary team (MDT) requirements are important to understand, to ensure the service is providing the best care, and will assist improving the service moving forwards. The aim of this study is to describe the clinic population in a novel post-COVID clinic population of CYP and to evaluate the service provided. Methods: All patients presenting to the service between April 2021 to January 2022 were included. Data collected for each patient included demographics including sex and age, pre-morbid medical and psychological conditions, COVID-19 patient and family history, physical and emotional symptoms, severity scores, symptom duration and management. All patients referred to the service are discussed with referrer at a virtual MDT meeting and management given. Duration from referral to discussion at MDT, together with MDT outcome and ongoing management was recorded. Patient demographics and symptom profiles were collected by the clinical team. Data were analysed using descriptive statistics. Results: 68 referrals were accepted by the Pan-London Children and Young People Post-COVID Service between April 2021 and January 2022. The majority of patients are of white ethnicity (38%) followed by Asian/Asian British ethnicity (10%). The mean age of the patients referred to the clinic is 13.5 with a range of 7 years old to 18 years old. There are more female (58%) than male (41%) patients. There was no difference in mean age of male and female participants (t=0.11, p=0.92). The most common symptoms were fatigue (87.88%), headaches (69.70%), anxiety (60.61%), and brain fog (54.6%). Shortness of breath occurred in 33%, usually dysfunctional breathing. 50% of patients had a pre-existing medical or mental health condition. Conclusion: This study describes the CYP patients presenting to a novel tertiary post-COVID service. This is an emerging group for whom symptom aetiology and best management strategies are still being established. Our data highlighted the range of patients presenting to the service, and the complexity of symptoms causing significant functional disruption to their lives. These results support the need for an MDT service that can tailor care of these patients and offer management with the best clinical outcomes. Reference: Recent WHO Delphi consensus re 'Post-Covid Condition' https://www.who.int/publications/i/item/WHO-2019-nCoV-Post_COVID-19_condition-Clinical_case_definition-2021.1